PURITANISME DAN FUNDAMENTALISME DALAM ISLAM TRANSNASIONAL SERTA IMPLIKASINYA TERHADAP PANCASILA SEBAGAI IDEOLOGI BANGSA - Rendy Adiwilaga (Journal of Governance, 2017)
In fact, the movement of Islamisme has special portion in the political world. It not only presents as a potential power, this movement is also there as a good bargain to define and colorise the political climate. The movement not only exists as antithesis to the old concept created by the western, but also it appears as a movement to influence the colors of the political states in many countries, particularly in the newly independent states after the World War II. This present article explains how, historically, the Ideology of Islam Transnational as the idology that spread over in Indonesia after reformation movement builds a new hegemony. It also describes how this ideology influences the Pancasila, especially the existence of Pancasila as the national concensus.